Nano-TiO2 stability in medium and size as important factors of toxicity in macrophage-like cells. (February 2019) - Brzicova, T.; Sikorova, J.; Milcova, A.; Vrbova, K.; Klema, J.; Pikal, P.; Lubovska, Z.; Philimonenko, V.; Franco, F.; Topinka, J.; Rossner, P.
Abstract: TiO2 along with nano-TiO2 are commonly found in consumer products. In vivo studies have observed an accumulation of nano-TiO2 in macrophages. However, characteristics of nano-TiO2 determining toxicity remain unclear. In our study, the cytotoxic effects of 14 diverse nano-TiO2 on THP-1 macrophage-like cells were measured by 3 cytotoxicity assays (MTS, WST-1 and LDH). Total averaged cytotoxicity was calculated using principal component analysis. Characteristics of all 14 nano-TiO2 included hydrodynamic diameter, zeta potential, shape, polydispersity index (PDI) and concentration; moreover, crystal form, specific surface area and crystallite size were measured for 10 nano-TiO2 . The variables affecting cytotoxicity were chosen using LASSO (least absolute shrinkage and selection operator). Except for concentration, PDI in media measured within 1 h after preparation of the nanomaterial dispersion was selected as a variable affecting cytotoxicity: stable dispersion resulted in higher cytotoxic effects. Crystallite size has been shown to have nonlinear effects (particles of sizes between 20 and 60 nm were cytotoxic while smaller and larger ones were not) and thus it has been excluded from LASSO. The shape (particles/fibre) and crystal form did not affect the cytotoxicity. PDI and the nonlinear effect of size could be an explanation for the inconsistencies of the cytotoxicity of nano-TiO2 in various studies. Graphical abstract: Highlights: Physical factors affecting cytotoxicity of nano-TiO2 in THP-1 cells were studied Concentration and polydispersity index measured within 1 h affected cytotoxicity Particles of 20–60 nm were cytotoxic while smaller and larger ones were not No significant difference between anatase/rutile crystallinity was found Overall cytotoxic effects of nano-TiO2 in THP-1 macrophage-like cells were low